ENTREPRENEURSHIP MANAGEMENT OF DARUL FIKRI ISLAMIC BOARDING SCHOOL BASED ON RELIGIOUS TOURISM - Hasanudin Hasanudin; Ariefanda Iqbal Perdhana; Supriaman Supriaman (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
A pesantren with the aim of exploring entrepreneurship education, as well as supporting Islamic education and religious spirituality in entrepreneurship education, employs methods and activities that support the creation of knowledge, competencies, and experiences that enable students to take the initiative and participate in the creation of entrepreneurial value based on Islamic values. A student must possess entrepreneurial character to be able to create a business opportunity when they enter society. Entrepreneurial character can be shaped in various ways, one of which is through pesantren. Pesantren serves as a place for students to directly learn about entrepreneurship and the application of economics in accordance with Islamic law. The presence of pesantren business units is expected to equip students with various skills in line with the demands of the times. The aim of this research is to understand the role of pesantren business units in shaping the entrepreneurial character of students and to identify the factors influencing entrepreneurship development in Darul Fikri Pesantren. This research uses a qualitative research approach. Data collection techniques include observation, interviews, documentation, and a combination/triangulation of these methods. Data is analyzed by reducing irrelevant data, presenting the data, and drawing conclusions. The research concludes that the role of pesantren has an impact on shaping entrepreneurial character. The factors influencing religious tourism development include funds, natural resources, the community, government policies, labor, private sector involvement, tourism object potential, and promotion.